2013
DOI: 10.1590/s1415-790x2013000100011
|View full text |Cite
|
Sign up to set email alerts
|

Fatores que influenciam a satisfação do paciente ambulatorial em uma população de baixa renda: um estudo de base populacional

Abstract: The present study revealed a high prevalence of satisfaction with medical consultations and a significant positive association between satisfaction and the location of consultation (health plan-affiliated or private services).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 17 publications
1
13
0
5
Order By: Relevance
“…Under the Hearing Assessment domain, the higher the users' economic classification, the higher user satisfaction. This was also found by a study that revealed that users with higher family income were more satisfied with the medical consultation and its scheduling process (28) .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Under the Hearing Assessment domain, the higher the users' economic classification, the higher user satisfaction. This was also found by a study that revealed that users with higher family income were more satisfied with the medical consultation and its scheduling process (28) .…”
Section: Discussionsupporting
confidence: 54%
“…In this study, it was observed that an increase in self-reported hearing impairment is correlated with higher satisfaction as to communication and information received by the service's professionals. This may show that users with a higher degree of impairment receive differentiated attention on the part of professionals, allowing for better communication and user-professional dialog and, consequently, greater adequacy of communication to the patient's sociocultural particularities (23,(26)(27)(28)(29) . Therefore, providing appropriate attention may have positive effects in the user satisfaction assessment, as it is an important measure in health care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering such characteristics as income proxy, the effects are similar to those presented by studies among adults 24 . Research indicates that individuals belonging to lower income groups seek less health services regardless of age [25][26][27][28] . Data from the National Household Sample Survey (PNAD) indicate an increase in the use of health services and point to a reduction in the inequalities of access to primary health care [29][30] , but such inequalities persist, mainly in relation to income.…”
Section: Discussionmentioning
confidence: 99%
“…21 Waiting time has been reported as a very important contributing factor to client satisfaction regarding healthcare services. [22][23][24] It has been suggested in other studies that waiting time not only has a negative impact on users but also on healthcare providers. 25 In this study most of women spent an hour on average travelling to FP services.…”
Section: Discussionmentioning
confidence: 99%